2015
DOI: 10.5858/arpa.2014-0511-sa
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Diagnostic Error Reduction in Surgical Pathology and Cytology: Guideline From the College of American Pathologists Pathology and Laboratory Quality Center and the Association of Directors of Anatomic and Surgical Pathology

Abstract: Context.-Additional reviews of diagnostic surgical and cytology cases have been shown to detect diagnostic discrepancies.Objective.-To develop, through a systematic review of the literature, recommendations for the review of pathology cases to detect or prevent interpretive diagnostic errors.Design.-The College of American Pathologists Pathology and Laboratory Quality Center in association with the Association of Directors of Anatomic and Surgical Pathology convened an expert panel to develop an evidencebased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 125 publications
0
42
1
Order By: Relevance
“…Although focused double review was an effective pre-signout intervention for interpretative error reduction, the authors also emphasized the importance of conference review as a post-sign-out mechanism of detection of interpretative errors (80%) and detection of all types of error (10%-20%). 8 In comparison to these 2 prior studies, we found a higher amendment rate, which likely reflects exclusive focus on breast specimens, an academic practice setting, and frequent second review of cases at the time of ancillary studies. A recent evidence-based guideline by the College of American Pathologists Pathology and Laboratory Quality Center and the Association of Directors of Anatomic and Surgical Pathology emphasized the value of double review in surgical pathology and cytology.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Although focused double review was an effective pre-signout intervention for interpretative error reduction, the authors also emphasized the importance of conference review as a post-sign-out mechanism of detection of interpretative errors (80%) and detection of all types of error (10%-20%). 8 In comparison to these 2 prior studies, we found a higher amendment rate, which likely reflects exclusive focus on breast specimens, an academic practice setting, and frequent second review of cases at the time of ancillary studies. A recent evidence-based guideline by the College of American Pathologists Pathology and Laboratory Quality Center and the Association of Directors of Anatomic and Surgical Pathology emphasized the value of double review in surgical pathology and cytology.…”
Section: Discussioncontrasting
confidence: 56%
“…As previously mentioned, breast was one of the most common organ sites with total amendments, misinterpretations, and misidentifications, second only to skin. 7 Meier et al 1,8 reported a single institution experience in the development and validation of amended report taxonomy and implementation of a real-time amended reportmonitoring system and lean process-improvement program. Amendment rates increased from 2.6 to 4.8 per 1000 during the validation period to 10.1 per 1000 during the initial phases of monitoring and subsequently decreased to 5.6 per 1000 once lean processes took hold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAP's and the ADASP's recently released results of the novel Interpretive Diagnostics Error Reduction Project offer practicing anatomic pathologists the following insightful recommendations to minimize errors [22]: timely mandatory and routine case review tailored to each anatomic pathology lab, followed by investigation of "problematic" cases wrought by significant pathologist disagreements and meaningful steps to investigate and rectify the discordance. While work is underway to prevent medical errors and to design procedures for handling them when they occur, managing communication about errors awaits further exploration in the pathology professionalism literature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nakhleh and colleagues suggested that "the test cycle in surgical pathology and cytology is similar to the test cycle of other laboratory tests" [4]. In fact, the testing process is always composed of the pre-analytic, analytic and post-analytic phases and although the brainto-brain loop model was developed specifically for laboratory medicine, it is useful for describing the general process of diagnostic testing [5].…”
mentioning
confidence: 99%